STEGANOGRAFI DENGAN METODE LSB (LEAST SIGNIFICANT BIT) DAN METODE MMB (MULTIPICATION-BASED BLOCK CIPHER) UNTUK PENGAMANAN DATA BERBENTUK TEKS - Agi Ayu Nurdianta Barus; Mutammimul Ula (Teknik Informatika Universitas Malikussaleh, 2015)
Security and confidentiality of data and information is the most important aspect of human activity undertaken. One way to maintain the security and confidentiality of personal data and the group is through cryptography and steganography techniques are believed to provide protection to the data and information held on the parties concerned. Through the incorporation of cryptography and steganography is expected to improve security on the data and information. This research was conducted by combining methods MMB on cryptography and steganography method of LSB in that run on Windows-based operating systems and can only hide a message with .txt format bitmap image format. MMB method is the development of IDEA method that uses 128 bit keys along the subblok divided into four pieces, each of which has a length of 32 bits. LSB method is a method that inserts the last bit of each pixel with a bit of the message.